2020
DOI: 10.1101/2020.03.30.20047308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Mortality Risk in Patients with COVID-19 Using Artificial Intelligence to Help Medical Decision-Making

Abstract: In the wake of COVID-19 disease, caused by the SARS-CoV-2 virus, we designed and developed a predictive model based on Artificial Intelligence (AI) and Machine Learning algorithms to determine the health risk and predict the mortality risk of patients with COVID-19. In this study, we used documented data of 117,000 patients world-wide with laboratory-confirmed COVID-19. This study proposes an AI model to help hospitals and medical facilities decide who needs to get attention first, who has higher priority to b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 9 publications
3
87
0
Order By: Relevance
“…Sputum, supraphysiologic RR, and decreased SpO 2 were directly related to pulmonary abnormalities in COVID-19. Elevated BUN, increased D-dimer, and lymphocytopenia might indicate extrapulmonary disorders and were potentially correlated with multiorgan damage caused by COVID-19 Available ML-based studies on prognosis prediction of COVID-19 patients are impeded by limited sample size, category of variables for prediction, short-term follow-ups for outcomes, and paucity of independent external validation [19][20][21][22][23][24][25][26] . To overcome these obstacles, we included 2520 consecutive inpatients with definite outcomes and detailed baseline characteristics within a specific time period for training and multiple validations of MRPMC to avoid overfitting and ensure general applicability, reproducibility, and credibility.…”
Section: Discussionmentioning
confidence: 99%
“…Sputum, supraphysiologic RR, and decreased SpO 2 were directly related to pulmonary abnormalities in COVID-19. Elevated BUN, increased D-dimer, and lymphocytopenia might indicate extrapulmonary disorders and were potentially correlated with multiorgan damage caused by COVID-19 Available ML-based studies on prognosis prediction of COVID-19 patients are impeded by limited sample size, category of variables for prediction, short-term follow-ups for outcomes, and paucity of independent external validation [19][20][21][22][23][24][25][26] . To overcome these obstacles, we included 2520 consecutive inpatients with definite outcomes and detailed baseline characteristics within a specific time period for training and multiple validations of MRPMC to avoid overfitting and ensure general applicability, reproducibility, and credibility.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the combination of quantitative analysis data, lung volumes, and structured report items, with the help of deep learning techniques, will enable digital patient models to be extracted; therefore, the progression of the disease and the possible response to pharmacological treatments could be studied from these predictive and prognostic models. For this reason, many research groups have launched single and multicenter studies for the application of artificial intelligence on CT data [6,33,[51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…34 In another study, neural networks trained on 42 clinical and demographic factors demonstrated 94% accuracy in predicting mortality. 35 • In identifying patients at risk of long term hospitalisation, a machine learning model trained on CT imaging data was able to identify such patients with predictive accuracy of 95%. 36 Perspectives MJA 213 (10) ▪ 16 November 2020 natural language processing applied to the PubMed database have identified a poly-ADP-ribose polymerase 1 inhibitor (CVL218) as a potential candidate, currently undergoing clinical testing.…”
Section: Prognostic Applicationsmentioning
confidence: 99%
“…Some ML algorithms can more accurately estimate risk of death, development of acute respiratory distress syndrome, and duration of hospitalisation (Box 3). [32][33][34][35][36]…”
Section: Predicting Risk Of Deterioration and Poor Outcomesmentioning
confidence: 99%